PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 56 PEKANBARU - Erlisnawati; Hendri Marhadi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
The problem addressed in this research is the low achievement of fourth-grade students in social science at SD Negeri 56 Pekanbaru, indicated by an average score of 60 and classical completeness of 40%, while the minimum completeness criterion was set at 70. The purpose of this study was to improve students’ social science achievement through the application of the cooperative learning model type Group Investigation. This research employed classroom action research consisting of two cycles with four procedures: planning, acting, observing, and reflecting, and each cycle comprised three meetings. The instruments used were syllabus, lesson plans, and student worksheets, while data collection instruments included observation sheets and tests. The collected data covered students’ learning outcomes and teacher activities during the learning process. After the implementation of the cooperative learning model type Group Investigation, students’ achievement in UH I reached an average score of 70.50, an improvement of 17.50% from the basic score, with classical completeness of 60%. In UH II, the average score increased to 80.83, showing an improvement of 34.72%, with classical completeness reaching 81.82%. Teacher activity in the first meeting of cycle I was 59.38% (fair category) and increased to 71.88% (good category) in the second meeting, while in cycle II it increased to 84.38% and 90.63% (very good category). Student activity in the first meeting of cycle I was 56.25% (fair category) and increased to 65.63% (good category) in the second meeting, then further increased in cycle II to 81.25% and 87.50% (very good category). Based on these results, it can be concluded that the implementation of the cooperative learning model type Group Investigation can improve social science learning outcomes of fourth-grade students at SD Negeri 56 Pekanbaru.